Breeding cowpea (Vigna unguiculata (L.) Walp.) for resistance to spotted pod borer (Maruca vitrata Fab.) - Ambavane Ajinkya Rajendra (Department of Plant Breeding and Genetics College of Horticulture, 2018)
Cowpea [Vigna unguiculata (L.) Walp.] is important pulse crop rich in nutrients, especially proteins. This crop is cultivated in the tropics of Asia, Africa and other parts of the world. Nevertheless, the production of cowpea is unable to achieve its summit. One of the prime reasons for this is the infestation of a notorious pest, the spotted pod borer, (Maruca vitrata Fab.; Lepidoptera: Crambidae). Spotted pod borer is one of the most important post-flowering pests of cowpea in the tropics. It is a major lepidopteran pest and damage cause to cowpea by the pest almost always crosses economic threshold level. Hence, the present investigation was conducted in the Department of Plant Breeding and Genetics, College of Horticulture, Vellanikkara, Kerala Agricultural University, Thrissur during 2015 to 2018 with the objective of identification and incorporation of resistance against spotted pod borer in high yielding varieties of cowpea and assessment of parental polymorphism at the molecular level Thirty genotypes of cowpea formed the material for the study. These genotypes were subjected to field screening against spotted pod borer. These genotypes were also evaluated for morphological and biochemical basis of resistance. Five selected genotypes from experiment 1 then hybridised with four high yielding genotypes viz., Geethika, Vellayani Jyothika, Lola and Kashi Kanchan following Line × Tester mating design. Twenty F 1 hybrids evaluated for field resistance and the morphological basis of resistance. Progenies of selected F 1 hybrids grown as F 2 populations and evaluated for same parameters as like F 1 s. Thirty genotypes were also subjected to molecular screening by 40 SSR primers. Wide variation was observed in terms of different damage parameters. Ten genotypes viz., Hridya, Palakkadan thandan payar, EC 300039, EC 98668, EC 101216, IC 52110, IC 39945, IC 2918, IC 39922 and IC 39916 recorded total damage below five per cent. Among them, IC 39922 observed to have no flower bud and flower damage, EC 300039, EC 98668, IC 52110, IC 39945, IC 2918 and IC 39916 recorded no flower damage, whereas, Palakkadan thandan payar, IC 39945, IC 2918 and IC 39947 were free from pod damage. The highest damage was recorded in the variety Bhagyalakshmy (48.46 %) followed by variety Lola (30.04 %). Analysis of the morphological basis of resistance to spotted pod borer revealed the negative correlation of trichome density and length on flower bud, trichome density on the pod and pod wall thickness with respective damage parameters. With respect to the biochemical basis of resistance to spotted pod borer, total sugar content, reducing sugar content and non-reducing sugar content of flower bud and pod showed a positive correlation with damage parameters, but the correlation was not significant. However, the total protein content of pod showed a strong and positive correlation with pod damage. Total phenol content of flower bud showed strong negative correlation with damage parameters. Polyphenol oxidase activity in flower bud and pod exhibited a strong negative correlation with damage parameters. The crude fibre content of pod also showed a strong negative correlation with pod damage. In experiment 3, three SSR primers viz., CLM0061, CLM0295 and CLM0300 recorded high polymorphic information content (0.70, 0.71 and 0.76, respectively). Primer CLM0190 observed to have high amplicon size (307.03-415.73 bp). Jaccard’s similarity coefficient was highest between IC 52118 and IC 39916 (0.643) and was lowest between Kashi Kanchan and TVX-944 (0.022). Cluster analysis of SSR data grouped 30 genotypes in 22 clusters, and the 21 st cluster was observed to have more members (3 genotypes). Most resistant genotype, IC 2918, grouped in a separate cluster which proved its diverse nature from other genotypes. Principal component analysis of SSR data placed three yard-long bean genotypes viz., Geethika, Vellayani Jyothika and Lola near to each other in a two-dimensional score plot. The same analysis also formed two clusters with more number of genotypes which placed resistant and susceptible genotypes separately. In field screening of F 1 hybrids, Hybrid 20 observed to have total damage below 5 per cent. Eight hybrids recorded total damage in the range of 5 to 10 per cent. These hybrids were selected for next experiment. Line × Tester analysis of F 1 s revealed Kashi Kanchan, EC 98668 and IC 2918 as a good combiner for resistance against spotted pod borer. Hybrid 5, Hybrid 6, Hybrid 10, Hybrid 11, Hybrid 13, Hybrid 15, Hybrid 16, Hybrid 17, Hybrid 18, Hybrid 19 and Hybrid 20 observed to have desired negative heterosis (mid-parent) for total damage. In F 2 plant screening, Hybrid 1 population recorded low mean for total damage (6.76 %), whereas, the population of Hybrid 3 recorded high mean (12.17 %). Around 100 plants of F 2 generation recorded total damage below ten per cent. Out of them, around 38 plants also registered good yield. These plants should be further evaluated to isolate high yielding resistant segregants.